2005
DOI: 10.1007/11574620_25
|View full text |Cite
|
Sign up to set email alerts
|

Seven Bottlenecks to Workflow Reuse and Repurposing

Abstract: To date on-line processes (i.e. workflows) built in e-Science have been the result of collaborative team efforts. As more of these workflows are built, scientists start sharing and reusing stand-alone compositions of services, or workflow fragments. They repurpose an existing workflow or workflow fragment by finding one that is close enough to be the basis of a new workflow for a different purpose, and making small changes to it. Such a "workflow by example" approach complements the popular view in the Semanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 30 publications
0
53
0
4
Order By: Relevance
“…With increasing repository sizes, new challenges arise for managing these collections of scientific workflows and for using the information collected in them as a source of expertsupplied knowledge [10,19]. Challenges include the detection of functionally equivalent workflows, grouping of work-flows into functional clusters, workflow retrieval, or the use of existing workflows in the design of novel workflows [36,34,33,4,18].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing repository sizes, new challenges arise for managing these collections of scientific workflows and for using the information collected in them as a source of expertsupplied knowledge [10,19]. Challenges include the detection of functionally equivalent workflows, grouping of work-flows into functional clusters, workflow retrieval, or the use of existing workflows in the design of novel workflows [36,34,33,4,18].…”
Section: Introductionmentioning
confidence: 99%
“…The development of "rigid" workflow modeling and design frameworks has recently been identified as a major bottleneck for scientific workflow reuse and repurposing [5]. We have found that this lack of flexibility is often due to the use of control-flow within workflows for managing, integrating, and analyzing inherently complex life-science data.…”
Section: Resultsmentioning
confidence: 99%
“…In this case it was word of mouth within one institution; this barrier needs to be overcome. So, we have a situation of workflows as reusable knowledge commodities, but with potential barriers to the exchange and propagation of those scientific ideas that are captured as workflow [11].…”
Section: The Workflow As a First Class Citizenmentioning
confidence: 99%